1980
DOI: 10.1038/clpt.1980.88
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between saliva salicylate concentration and free or total salicylate concentration in serum of children with juvenile rheumatoid arthritis

Abstract: Our purpose was to determine the feasibility of using salicylate (SA) concentrations in saliva as an indirect measure of SA concentrations in serum of children with juvenile rheumatoid arthritis. Sixty‐four paired blood and saliva samples were obtained from 17 children, 4 to 17 yr of age (average, 9 yr), who were receiving aspirin every 8 hr. Serum total (free and bound) SA concentrations ranged from 5 to 36 mg/100 ml. The fraction of free (unbound) SA in serum, determined by equilibrium dialysis against an eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Based on the good correlation between saliva con centrations in saliva and plasma in small number of subjects, several reports suggested that determination of salicylate in saliva may be useful in the monitoring of salicylate thera py [140-143]. A more extensive study in chil dren with juvenile rheumatoid arthritis con firmed the correlation between saliva and both free and total serum salicylate concentra tions, but a considerable intrasubject variabil ity in the saliva/serum salicylate concentra tion ratio was found [64],…”
Section: Salicylatementioning
confidence: 99%
“…Based on the good correlation between saliva con centrations in saliva and plasma in small number of subjects, several reports suggested that determination of salicylate in saliva may be useful in the monitoring of salicylate thera py [140-143]. A more extensive study in chil dren with juvenile rheumatoid arthritis con firmed the correlation between saliva and both free and total serum salicylate concentra tions, but a considerable intrasubject variabil ity in the saliva/serum salicylate concentra tion ratio was found [64],…”
Section: Salicylatementioning
confidence: 99%
“…The utility of salivary salicylate determinations as a convenient and non-invasive indirect means of monitoring free salicylate concentrations in serum has recently been explored in a group of children with juvenile rheumatoid arthritis (Levy et al, 1980 DR BRUNE said that in the autoradiographic study reported he used a tritium label in the acetyl moiety, and in this particular situation there was a visible degree of labelling detected in the bone marrow compartment. He pointed out that aspirin acetylates cyclo-oxygenase, and speculated that it would occur in megakaryocytes, although there was at present no proof.…”
Section: Implications For Pharmacokinetic Monitoringmentioning
confidence: 99%
“…There is evidence from animal studies that this concept applies to salicylic acid (Reynolds & Cluff, 1960). As plasma protein binding of salicylate is concentration dependent, variable between individuals and affected by disease (evidence reviewed by Levy, Procknal, Olufs & Pachman, 1980), it is preferable in principle to monitor free rather than total salicylate concentrations in plasma or serum. However, determination of free drug in these fluids is time-consuming and costly, and therefore not suitable for routine clinical use with presently available methods.…”
Section: Implications For Pharmacokinetic Monitoringmentioning
confidence: 99%
“…Pharmacokinet. 21 (2) 1991 variation (coefficient of variation = 24%) in the ratio of mean saliva to serum salicylate concentrations (range of ratios 0.36 to 0.86) [Levy et al 1980). This is attributable, in part, to variation in salivary pH, to which salicylate concentrations are sensitive.…”
Section: Salicylalesmentioning
confidence: 98%